From Protection to Justification: Distorting Maqāṣid al-Sharīʿah in Child Marriage - Kamba, Sri Nanang Meiske; Thalib, Mutia Cherawaty; Mustika, Waode; Sarson, Moh. Taufiq Zulfikar (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
This article investigates the distortion of maqāṣid al-sharīʿah within the practice of child marriage in Indonesia, where a normative framework intended to safeguard protection is increasingly reinterpreted as a mechanism for social legitimation. This research seeks to critically examine the selective deployment of maqāṣid al-sharīʿah in judicial decisions on marriage dispensation and to uncover internal tensions among the objectives of Islamic law concerning child welfare protection. We employ a normative legal research design using conceptual and case-based approaches drawing upon statutory regulations, court rulings, and both classical and contemporary maqāṣid literature. The findings reveal that judicial reasoning in dispensation cases tends to overemphasize the protection of honor (ḥifẓ al-‘ird) while marginalizing essential safeguards such as life (ḥifẓ al-nafs) and intellect (ḥifẓ al-‘aql). This pattern produces a pseudo-maqāṣid phenomenon and reflects underlying power relations in legal construction shaped by prevailing social pressures. This study concludes that a methodological reconstruction is required for the application of maqāṣid through a hierarchical and contextual framework that prioritizes child protection, ensuring that Islamic law operates as an instrument of substantive justice rather than mere normative legitimacy within the Indonesian judicial practice.